Gut microbiota modulation in cardiac cell therapy with immunosuppression in a nonhuman primate ischemia/reperfusion model - Hung-Chih Chen; Yu-Che Cheng; Marvin L. Hsieh; Po-Ju Lin; Emily F. Wissel; Theodore Steward; Cindy M. C. Chang; Jennifer Coonen; Timothy A. Hacker; Timothy J. Kamp; Patrick C. H. Hsieh (npj Regenerative Medicine)
Abstract Gut microbiota affect transplantation outcomes; however, the influence of immunosuppression and cell therapy on the gut microbiota in cardiovascular care remains unexplored. We investigated gut microbiota dynamics in a nonhuman primate (NHP) cardiac ischemia/reperfusion model while under immunosuppression and receiving cell therapy with human induced pluripotent stem cell (hiPSC)-derived endothelial cells (EC) and cardiomyocytes (CM). Both immunosuppression and EC/CM co-treatment increased gut microbiota alpha diversity. Immunosuppression promoted anaerobes, such as Faecalibacterium, Streptococcus, Anaerovibrio and Dialister, and altered amino acid metabolism and nucleosides/nucleotides biosynthesis in host plasma. EC + CM cotreatment favors Phascolarctobacterium, Fusicatenibacter, Erysipelotrichaceae UCG-006, Veillonella and Mailhella. Remarkably, gut microbiota of the EC/CM co-treatment group resembled that of the pre-injury group, and the NHPs exhibited a metabolic shift towards amino acid and fatty acid/lipid biosynthesis in plasma following cell therapy. The interplay between shift in microbial community and host homeostasis during treatment suggests gut microbiome modulation could improve cell therapy outcomes.